Mapping stakeholder expectations in a digital business : case Pinja Group - Vasileva, Valeriia (2021)
Corporate sustainability has emerged as an essential topic in the business world and academic discussion. Nowadays, companies from different industries pay more vigorous attention to their social, economic, and environmental impacts. At the same time, a shareholder-centric approach shifted towards a stakeholder-oriented approach, requiring businesses to listen and respond to stakeholder expectations. Despite the increasing importance of corporate sustainability and the role stakeholders play in it, there is limited research in this field in the context of the digital industry.